Optimizing the synergistic effect of organic and inorganic fillers on fire-retardant and mechanical properties of vinyl ester/flax bio-composites - Faraz, Muhammad Iftikhar (Frontiers in Materials, 2024)
Vinyl ester/flax (VE/flax) bio-composites were made after incorporating hybrid concentrations (0, 3, and 6 % by weight (wt)) of halloysite nanotubes (HNT), magnesium hydroxide (MHO) and chitosan infused ammonium polyphosphate (CAP) particles. The purpose of incorporation of these particles was to improve the fire-retardant (FR) properties of the VE/flax composite; however, its effect on mechanical properties was also evaluated. To reduce the number of experiments (from 27 to 9), Taguchi design of experiment was employed during composite fabrication phase. Initially, the burning time and burning rate of all the composites were calculated using a horizontal burning test while tensile properties were determined using a tensile test. To predict an optimum composition, a signal to noise (S/N) ratio analysis of the burning time and tensile strength was conducted as "larger is better" criteria. The combination of 6% MGO and 3% CAP was predicted to be an optimum hybrid filler for enhanced fire retardancy, while VE/flax composite with no filler proved to have the highest tensile strength. HNT was found to be the least effective filler for both tensile and fire-retardant properties. The predicted composition was then fabricated and validated through experimental characterizations. The fireretardant properties of the optimized composite were additionally assessed using a limiting oxygen index (LOI) test and thermal stability was evaluated using a thermogravimetric analysis (TGA). The burning time of the optimized composite was found to be delayed by 46.5% of that of VE/flax composite, while its thermal degradation was 11.23% lower than VE/flax composite.